PEMENDEKAN PADA KATA PINJAMAN (GAIRAIGO) DALAM BAHASA JEPANG - Maylita, Deasy; Aibonotika, Arza; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstarct: This study described the types and abbreviation processes of Japanese loanwords (gairaigo). The background of this study is the origin form of the loanwords (gairaigo) that has shortened by Japanese people are difficult to understand for foreigners. The shortened loanwords (gairaigo) in the sentences of online data corpus Kotonoha (http://www.kotonoha.gr.jp) was chosen as the data of this study. The theory used in this study are the types of abbreviation theory by Kridalaksana (2007) and abbreviation processes of Japanese loanwords (gairaigo) by using theory of Labrune (2002) with qualitative descriptive approach. The result of this research are (1) found three types of Japanese loanwords (gairaigo) abbreviation, which is: clipping, acronym, and contraction (2) abbreviation processes of Japanese loanwords (gairaigo), clipping have eight abbreviation processes, acronym have two abbreviation processes, and contraction have one abbreviation process. The shortened word in the clipping form are mostly found because this type is more diverse than the other shortening types.Key Words: loanwords, abbreviation, clipping, acronym, contraction